ANALISIS RASIO PROTEKSI ANTIULSER SARI BUAH PEPINO (Solanum muricatum Aiton) MENGGUNAKAN MENCIT SEBAGAI MODEL HEWAN COBA - Nyi Mekar Saptarini; Dadan Suryasaputra; Atep Misbah Saepulhak (Faculty of Pharmacy, Universitas Gadjah Mada, 2011)
Peptic ulcer were been caused by an imbalance between the aggressive factors and a number of defense mechanisms. Pepino (Solanum muricatum Aiton) fruit predicted had antiulcer activity. This study is aimed to test the antiulcer activity of pepino fruit juice in Swiss-Webster mice model which induced by 50 µL concentrated acetic acid. The steps in this study consist of making of fruit juice, phytochemical screening, testing of antiulcer activity at 300, 500, dan 800 µL/20 g BW in doses, and data analyzed using ANOVA. The concentration of pepino fruit juice was 2.5 g/mL. Phytochemical screening showed that pepino fruit juice contain alkaloids, flavonoids, and tannins with protection ratio were 6.02, 23.15, and 63.29% at 300, 500, dan 800 µL/20 g BW, respectively.